2009
DOI: 10.4141/cjps08231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of habitat fragmentation on the genetic diversity of Stipa krylovii Reshov. in an agro-pastoral ecotone in northern China

Abstract: Z. 2009. Effect of habitat fragmentation on the genetic diversity of Stipa krylovii Reshov. in an agro-pastoral ecotone in northern China. Can. J. Plant Sci. 89: 875Á882. Native grassland in China have been fragmented due to the introduction of agriculture, which has the potential to reduce genetic diversity. In order to understand the potential effects of fragmentation, we conducted a study to examine the genetic diversity between two populations of Stipa krylovii in a typical steppe ecoregion, in northern Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A study of Argyroxiphium sandwicense ssp. sandwicense on the island of Hawaii indicated that diversity was closely related to environmental differences; the pressure of natural selection was strong, and the genetic diversity was high (Friar et al 2010;Zheng et al 2010). Since the third century, climate change has produced variable and complex environmental conditions for C. japonica (Naidong).…”
Section: Relationships Among C Japonica Populationsmentioning
confidence: 99%
“…A study of Argyroxiphium sandwicense ssp. sandwicense on the island of Hawaii indicated that diversity was closely related to environmental differences; the pressure of natural selection was strong, and the genetic diversity was high (Friar et al 2010;Zheng et al 2010). Since the third century, climate change has produced variable and complex environmental conditions for C. japonica (Naidong).…”
Section: Relationships Among C Japonica Populationsmentioning
confidence: 99%